Web-based low–cost rooftop solar power plant for household application - Angga Wahyu Aditya; Nur Rani Alham; Restu Mukti Utomo (Jurnal POLIMESIN, 2023)
The global warming issue has been resolved through Sustainable Development Goals (SDGs) agreed upon by the world. One of the SDGs is affordable and clean energy. Green energy, such as solar energy, is a solution to realize it. Solar energy has massive potential as renewable energy in tropical countries. On the one side, solar energy is an excellent renewable energy. On the other side, solar energy has a low maturity level of technology. It is proven by the extravagant investment cost of building a solar power plant. Indonesia has an investment cost of up to 1200 USD per kWh, which is unsuitable for household applications. This investment cost will continue to be higher when it uses an IoT system for monitoring or managing the solar power plant. The low-cost solar power plant was designed using a hybrid system to reduce the investment cost. The industrial standard components include ACS712 as a current sensor, ZMPT101B as an AC voltage sensor, and ESP32 as a data processor and IoT module. The Blynk platform, connected to ESP32, is a web-based monitoring system. The success parameter consists of the DC voltage and current from battery and solar panel, AC voltage and current from single phase inverter. The low-cost solar power plant is designed in a 1.92 kWh battery pack with 1 kWh of AC continuous output power with total investment cost 1080 USD. The proposed solar power plant design decreases an investment cost by 14.29% up to 50.00 % per kWh.